Expert F# - Cisternino, Antonio; Granicz, Adam; Syme, Don (Apress : Imprint: Apress, 2007)
Expert F# is about practical programming in a beautiful language that puts the power and elegance of functional programming into the hands of .NET developers. In combination with .NET, F# achieves unrivaled levels of programmer productivity and program clarity. This books serves as The authoritative guide to F# by the designer of F# A comprehensive reference of F# concepts, syntax, and features A treasury of expert F# techniques for practical, real-world programming While inspired by OCaml, F# isn't just another functional programming language. Drawing on many of the strengths of both OCaml and .NET, it's a general-purpose language ideal for real-world development. F# integrates functional, imperative, and object-oriented programming styles so you can flexibly and elegantly solve programming problems, and brings .NET development alive with interactive execution. Whatever your background, you'll find that F# is easy to learn, fun to use, and extraordinarily powerful. F# will help change the way you think about and go about programming. Written by F#'s designer and two active contributors, Expert F# is the authoritative, comprehensive, and in-depth guide to the language and its use. Designed to help others become experts, the book gives a thorough introduction to the F# language from quick essentials to in-depth advanced topics such as active pattern matching, aggregate data types and operators, sequence expressions, lazy values, mutable data and side-effects, generics, type augmentations, functional decomposition and code organization. The second half of the book is devoted to examining the practical application of F#, providing elegant solutions to common programming tasks including user interface implementation, data access, web and distributed programming, symbolic and numerical computations, concurrent programming, testing, profiling, and interoperability with other languages. The latest hot developments in F# and .NET are also addressed, including Active Patterns, implicit class construction, integration with LINQ over relational data, meta programming and useful tips for working with Visual Studio and F# command-line tools. The worlds foremost experts in F# show you how to program in F# the way they do!